The influence of exercise training volume alterations on the gut microbiome in highly-trained middle-distance runners. Issue 8 (3rd August 2022) - Craven, Jonathan; Cox, Amanda J.; Bellinger, Phillip; Desbrow, Ben; Irwin, Christopher; Buchan, Jena; McCartney, Danielle; Sabapathy, Surendran
ABSTRACT: The aim of this study was to determine the influence of training volume alterations on diversity and composition of the gut microbiome in a free-living cohort of middle-distance runners. Fourteen highly-trained middle-distance runners ( n = 8 men; V ˙ O2peak = 70.1 ± 4.3 ml·kg·min −1 ; n = 6 women, V ˙ O2peak : 59.0 ± 3.2 ml·kg·min −1 ) completed three weeks of normal training (NormTr), three weeks of high-volume training (HVolTr; a 10, 20 and 30% increase in training volume during each successive week from NormTr), and a one-week taper (TaperTr; 55% exponential reduction in training volume from HVolTr week three). Faecal samples were collected before and immediately after each training phase to quantify alpha-diversity and composition of the gut microbiome. A three-day diet record was collected during each training phase and a maximal incremental running test was completed after each training phase. Results showed no significant changes in nutritional intake, alpha-diversity, or global microbial composition following HVolTr or TaperTr compared to NormTr ( p 's > 0.05). Following HVolTr, there was a significant decrease in Pasterellaceae ( p = 0.03), Lachnoclostridium ( p = 0.02), Haemophilus ( p = 0.03), S. parasagunis ( p = 0.02), and H. parainfluenzae ( p = 0.03), while R. callidus ( p = 0.03) significantly increased. These changes did not return to NormTr levels following TaperTr. This study shows that the alpha-diversity and global composition of the gut microbiome were unaffected by changes in training volume. However, an increase in training volume led to several changes at the lower taxonomy levels that did not return to pre-HVolTr levels following a taper period.